পহেলা বৈশাখ বাঙলি ঐতিহ্যের বাহক - Māhamuda, Ānu. (ঢাকা: ঐতিহ্য, 2001)
Articles chiefly on Bengali new year and folk festivals related to it; includes articles on Bengali folk culture.
Includes bibliographical references.
In Bengali.
Keywords: Folk festivals -- India -- Bengal; Bengali (South Asian people) -- Folklore; Bengal (India) -- Social life and customs